Predictors of Local Consumers Green Purchase Intention Toward Suputra Herbal Incense Produc ts in Badung Regency - Pande Kadek Dilla Maharani (Digital Innovation : International Journal of Management, 2025)
Public awareness of environmental issues is increasing, but there is still a gap between ecological understanding and green consumption behavior. This phenomenon is evident in the low interest of local consumers in Suputra Herbal Incense products in Badung Regency, despite the product's strong ecological and cultural value. This condition raises questions about the factors influencing local consumers' green purchasing intentions towards environmentally friendly products. This study uses a quantitative approach with a causal associative design to analyze the main predictors influencing green purchasing intentions. A total of 100 respondents were selected through a purposive sampling technique, namely potential consumers who are related to herbal incense products. The research instrument has been tested for validity and reliability, thus it is suitable for use in data collection. Data analysis was conducted with the help of multiple linear regression using SPSS software to test the research hypotheses. The results show that green brand image, green marketing, and price perception have a positive and significant influence on local consumers' green purchasing intentions. These findings confirm that an environmentally friendly brand image can strengthen consumer trust and interest. In addition, a consistent and authentic green marketing strategy plays a significant role in increasing product appeal. The perception of fair pricing is also a key consideration, as consumers tend to be more accepting of prices when they align with the product's ecological benefits and cultural values. In conclusion, this research provides practical contributions for MSMEs, particularly in designing effective and sustainable green marketing strategies. Efforts to strengthen green brand image, consistently implement environmentally friendly promotions, and foster a perception of fair pricing will encourage increased purchasing intentions among local consumers. Thus, eco-friendly products like Suputra Herbal Incense have the potential to compete more strongly in the increasingly competitive domestic market. Keywords: Green Purchase Intention, Green Brand Image, Green Marketing, Perceived Price, MSMEs